(untitled) (African Journal of Biomedical Research, 2023)
Exposure to Pirimiphos-methyl (POM) has been reported to adversely affect sperm functions, leading to male infertility. This study seeks to investigate the effect of resveratrol on POM induced male reproductive dysfunction. Twenty-four male Sprague-Dawley rats weighing between 165g – 200g were randomly divided into four groups of control, the POM group (received 62.5mg/kg POM/ b.w), POM + RES (received 62.5mg/kg POM and 20mg/kg body weight of resveratrol, and the RES group (received 20mg/kg body weight resveratrol) for 65 days. The results showed a significant decrease in body weight gain in the POM group, POM +RES group compared to the control. The relative liver weight of the POM group was also significantly increased compared with the control (p<0.05). RES + POM significantly increased the epididymal sperm count, motility, morphology, and testosterone level compared to the POM group. POM increased MDA and reduced SOD, GSH, and catalase activities, while POM + RES only reversed this trend in the MDA, catalase, and SOD levels. There was a significant increase in the cholesterol concentration of the POM group compared to the control while there were no significant differences in the HDL, LDL, and triglyceride levels across all the groups. There was distortion in the POM group’s cytoarchitecture of the liver and testes compared to the control and RES groups. In conclusion, the results showed that POM disrupts sperm functions and caused hepatotoxicity in rats’ livers. This study also shows that RES improves sperm parameters impaired by POM.